La coscienza cristiana basica e la speranza cristiana - Woodall, George J. (Alpha Omega, 2012)
The article conducts a reflection on moral conscience and on prayer in relation to the ‘great hope’, rooted in the salvation, which is offered to us in Jesus Christ. A concept which was proposed in the aftermath of the second Vatican Council, that of a ‘basic Christian conscience’, is compared with the concept of the role of anamnesis of conscience, as suggested by Josef Ratzinger, and with the indications of Spe salvi, to specify the structures and the contents of such a basic Christian conscience, in such a way as to avoid its being applied by means of proportionalism. In this context, the conscience of the Christian believer is compared with that of the non-believer, in the light both of the concept of the ‘great hope’ elaborated by Benedict XVI in the encyclical and of the conscience of the non-believer, examined by him as the theologian, Josef Ratzinger. The role of prayer, as a ‘place of Christian hope’, implies here also an exercise of conscience, although prayer and conscience cannot be identified with each other. The reflection requires, finally, a careful evaluation of the relationship between a basic Christian conscience and the role of conscience in judging our acts of every day, where the temptation to try to resolve any conflicts which may arise by way of proportionalism is rejected.